DNA-Dependent RNA Polymerase from Yeast Mitochondria - Tsai, Ming-Jer (1971)
The DNA-dependent RNA polymerase present in the mitochondria of Saccharomyces cerevisiae has been solubilized using a 0.5 M KCI solution, and the soluble enzyme has been purified. Two forms of mitochondrial enzyme were obtained; they differ in their template specificity and metal-ion dependency. The mitochondrial RNA polymerase also differs from enzyme obtained from the nucleus with respect to antibiotic sensitivity and template specificity. Only the nuclear enzyme is sensitive to α-amanitin inhibition. The relative activities of the isolated nuclear and mitochondrial polymerases toward their homologous DNAs are consistent with their in vivo functions. The possibilities of bacterial- and nuclear-enzyme contamination of the mitochondrial enzyme preparation have been ruled out. RNA polymerase activity in two petite mutants has been studied. Isolated mitochondria from a petite mutant with no detectable mitochondrial DNA has greatly diminished mitochondrial DNA-dependent RNA polymerase activity, while a petite mutant with only a small change in mitochondrial DNA base composition has normal amounts of enzyme.